2005
DOI: 10.1158/0008-5472.can-05-0312
|View full text |Cite
|
Sign up to set email alerts
|

Tunicamycin Enhances Tumor Necrosis Factor–Related Apoptosis-Inducing Ligand–Induced Apoptosis in Human Prostate Cancer Cells

Abstract: Death receptor 5 (DR5/TRAIL-R2) is an apoptosis-inducing membrane receptor for tumor necrosis factor-related apoptosis-inducing ligand (TRAIL/Apo2L). In this study, we showed that tunicamycin, a naturally occurring antibiotic, is a potent enhancer of TRAIL-induced apoptosis through upregulation of DR5 expression. Tunicamycin significantly sensitized PC-3, androgen-independent human prostate cancer cells, to TRAIL-induced apoptosis. The tunicamycinmediated enhancement of TRAIL-induced apoptosis was markedly blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
123
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(139 citation statements)
references
References 37 publications
14
123
2
Order By: Relevance
“…3A), suggesting that Wit A modulates DR5 expression at the transcriptional level. Recently, CHOP was shown to be involved in MG132-or tunicamycin-mediated DR5 upregulation, contributing to the sensitization of TRAIL-mediated apoptosis [14,15]. We found that the protein level of CHOP was significantly increased by Wit A treatment in a dose-dependent manner, but KDEL (Lys-Asp-Glu-Leu), an ER stress marker protein, was not altered (Fig.…”
Section: Chop Mediates Wit A-induced Dr5 Up-regulationmentioning
confidence: 66%
“…3A), suggesting that Wit A modulates DR5 expression at the transcriptional level. Recently, CHOP was shown to be involved in MG132-or tunicamycin-mediated DR5 upregulation, contributing to the sensitization of TRAIL-mediated apoptosis [14,15]. We found that the protein level of CHOP was significantly increased by Wit A treatment in a dose-dependent manner, but KDEL (Lys-Asp-Glu-Leu), an ER stress marker protein, was not altered (Fig.…”
Section: Chop Mediates Wit A-induced Dr5 Up-regulationmentioning
confidence: 66%
“…In a previous study, various small molecule compounds, such as tunicamycin, 14 were reported to transactivate the DR5 gene by the upregulation of CHOP. The inostamycin-induced increase in DR5 mRNA was suppressed in CHOP-knockdown HCT116 cells; however, DR5 protein expression was not suppressed.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the limitations of TRAIL-induced cytotoxicity, the combination of TRAIL with other small molecule compounds has been postulated as strategy to potentiate the cytotoxicity of TRAIL and its therapeutic applications. Indeed, it was reported that several chemotherapeutic agents and natural products, such as CDDP, 10 etoposide, 10,11 doxorubicin, 12 PS-341 (bortezomib), 13 tunicamycin, 14 rottlerin, 15 brandisianins, 16 silibinin 17 and sodium butyrate, 18 were succeeded to cause the sensitization of TRAIL-resistant tumor cells to TRAIL-induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Although studies have suggested that PRK-like ER kinase/eukaryotic translation initiation factor 2a/ATF4 signaling is more important than ATF6 in inducing CHOP, maximal induction of CHOP in the presence of both ATFs is required (19). Evidence indicates that activation of a CHOP-binding site on the DR5 promoter region accounts for DR5 gene transcription induced by MG132 (14), TM (20), and TG (9). 15dPGJ 2 is not only an endogenous agonist of PPAR-g (21) but also an ER stress inducer (22).…”
Section: Introductionmentioning
confidence: 99%